Is There a Single Right Interpretation? - Krausz, Michael (Penn State University Press, 2021)
Is there a single right interpretation for such cultural phenomena as works of literature, visual artworks, works of music, the self, and legal and sacred texts? In these essays, almost all written especially for this volume, twenty leading philosophers pursue different answers to this question by examining the nature of interpretation and its objects and ideals. The fundamental conflict between positions that universally require the ideal of a single admissible interpretation (singularism) and those that allow a multiplicity of some admissible interpretations (multiplism) leads to a host of engrossing questions explored in these essays: Does multiplism invite interpretive anarchy? Can opposing interpretations be jointly defended? Should competition between contending interpretations be understood in terms of (bivalent) truth or (multivalent) reasonableness, appropriateness, aptness, or the like? Is interpretation itself an essentially contested concept? Does interpretive activity seek truth or aim at something else as well? Should one focus on interpretive acts rather than interpretations? Should admissible interpretations be fixed by locating intentions of a historical or hypothetical creator, or neither? What bearing does the fact of the historical situatedness of cultural entities have on their identities? The contributors are Annette Barnes, Noël Carroll, Stephen Davies, Susan Feagin, Alan Goldman, Charles Guignon, Chhanda Gupta, Garry Hagberg, Michael Krausz, Peter Lamarque, Jerrold Levinson, Joseph Margolis, Rex Martin, Jitendra Mohanty, David Novitz, Philip Percival, Torsten Pettersson, Robert Stecker, Laurent Stern, and Paul Thom
Description based on online resource; title from PDF title page (publisher's Web site, viewed 21. Jun 2021)
Keywords: PHILOSOPHY / Criticism; Criticism; Hermeneutics